2023
DOI: 10.1108/cr-04-2023-0076
|View full text |Cite
|
Sign up to set email alerts
|

How phygital customers’ experience transforms the retail banking sector? Examining customer engagement and patronage intentions

Jitender Kumar,
Sudhir Rana,
Garima Rani
et al.

Abstract: Purpose Phygital emerges as a promising phenomenon, as it uses innovative technologies to connect digital spaces and physical places that provide customers with an interactive and unique experience. Drawing the stimuli–organism–response (S-O-R) framework, the study aims to examine the phygital customer experience by using key drivers and their effect on customer engagement (CE), trust (TRU) and patronage intentions (PI). Design/methodology/approach Data were obtained by using convenience sampling from 389 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…This value falls below the accepted threshold of 50%. These results suggest that the study is not significantly affected by common method variance, as confirmed by the findings of Kumar et al. (2024a, b, c).…”
Section: Methodssupporting
confidence: 76%
“…This value falls below the accepted threshold of 50%. These results suggest that the study is not significantly affected by common method variance, as confirmed by the findings of Kumar et al. (2024a, b, c).…”
Section: Methodssupporting
confidence: 76%
“…The attributes of the data collected are self-reported, which shows that common method bias (CMB) may be an issue for the validity of the outcomes. Therefore, Harman’s single factor was applied as a statistical procedure to confirm that there was no CMB in the dataset (Kumar et al. , 2023a; Kumar et al.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…The attributes of the data collected are self-reported, which shows that common method bias (CMB) may be an issue for the validity of the outcomes. Therefore, Harman's single factor was applied as a statistical procedure to confirm that there was no CMB in the dataset (Kumar et al, 2023a;Kumar et al, 2023b. On a sample of 422, the single factor extraction was 31.28%, less than the threshold value of 50%, indicating no CMB problem in this model (Kumar et al, 2023d).…”
Section: Common Methods Biasmentioning
confidence: 99%
“…Individuals' BI and AU were measured through four items (Pa nkowska, 2023; Acikgoz et al, 2023). Drawing from the research of Rani and Kumar (2023) and Kumar et al (2024aKumar et al ( , 2024bKumar et al ( , 2024c, adopting a seven-point Likert scale is a strategic approach to enhancing the reliability and accuracy of data collection methods. This choice is justified by the scale's ability to provide greater detail and sensitivity than its five-point counterpart, thus enabling a more comprehensive capture of respondents' attitudes and viewpoints.…”
Section: Instrument Development and Pretestingmentioning
confidence: 99%